Treatment of Bone Defects by Transplantation of Genetically Modified Mesenchymal Stem Cell Spheroids - Kayoko Yanagihara; Satoshi Uchida; Shinsuke Ohba; Kazunori Kataoka; Keiji Itaka (Molecular Therapy: Methods & Clinical Development, 2018)
Cell transplantation is promising for regenerative medicine. A combination of a three-dimensional spheroid culture system with gene transfection was developed to enhance the therapeutic effects of mesenchymal stem cell (MSC) transplantation. The spheroid cell culture system is based on micropatterned substrates composed of a regular array of 100-μm-diameter cell-adhesion areas coated with a temperature-responsive polymer, poly (N-isopropylacrylamide-co-methacrylic acid), which allows for spheroid detachment by simply cooling the plates. In this study, MSC spheroids were transfected with plasmid DNA encoding runt-related transcription factor 2 (Runx2) and tested for their ability to enhance bone regeneration. In vitro analyses revealed that osteogenic differentiation of the MSCs was enhanced by forming spheroids and was further promoted by Runx2 expression. The enhanced osteogenic differentiation was maintained under pathological conditions, such as hypoxia and inflammation. Transplanting Runx2-transfected MSC spheroids into bone defects on rat femurs induced significantly faster bone regeneration compared with nontransfected MSC spheroids or genetically modified MSCs from conventional monolayer culture. MSC migration into the bone defect area was enhanced by upregulation of cell-migration-related genes. In conclusion, genetically modified MSC spheroids are effective for enhancing bone regeneration, providing a promising option for cell transplantation therapy in the fields of regenerative medicine. Keywords: mesenchymal stem cell, spheroid, bone regeneration, cell transplantation, genetic modification, regenerative medicine